Rethinking Civic Participation in Democratic Theory and Practice - Dacombe, Rod (The Theories, Concepts and Practices of Democracy, 2018)
This book makes an important contribution to contemporary debates over the place of civic participation in democratic theory and practice. Drawing on a detailed case study of the Blackbird Leys area of Oxford, the book employs a novel empirical approach to ask whether widespread participation in civic life can enhance the prospects for democracy, given the low levels of participation which tend to exist in deprived areas. Throughout, it presents an account of participation rooted in the history and development of the case, in order to avoid the kinds of abstraction which are characteristic of many existing studies in the area. The book will appeal to scholars working on democratic theory in applied settings, and will be of interest to anyone concerned with inequalities in civic participation.